IDO: modelling a serious educational game based on hands on approach for training dementia carers - MaskeliÅ«nas, R; DamaÅ¡eviÄius, R; BlaÅ¾auskas, T; Paulauska, A; Paulauskas, L; Chiatti, C (International Journal of Engineering and Technology, 2018)
Dementia is one of the burdensome diseases in older age for which there is no cure known. The demand for carers of dementia patients is growing as the population ages. We analyse serious games as an approach to provide dementia carers with training on care related problem solving and modelling real-world cases. We present the behaviour model of improved care process by applying serious games, describe the design of the interactive serious game, its game mechanics, game environment, game actors and the motivation reinforcement mechanisms. The results of the initial evaluation performed by surveying the people caring for their elderly parents and elderly persons themselves, both healthy and showing early signs of dementia, and using the System Usability Score (SUS) questionnaire provided favourable response to the game. The use of an ICT-based gamification approach as part the training package for dementia care will be beneficial for direct care workers leading to long-term improvement of dementia care quality.Â Â